Controlling Dualism in Sharia Cooperative and Spirit of Institutional Progressivity - Mansur Efendi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2020)
Act no 1 of 2013 on micro-finance institution makes controlling dualism for a micro-finance institution, cooperative, including sharia cooperative. In that act, every micro-finance institution that operating its business must choose between a cooperative or limited liability company (PT) as a legal entity. According to the act on cooperative and act on the micro-finance institution, Sharia cooperative can be supervised by Finance Service Authority (OJK) or cooperative and micro-medium enterprise service. This dualism makes differences in how to determine controlling institutions for sharia cooperative. One of the contributing factors is the differences in controlling regulation between act on cooperative and act on the micro-finance institution. The result of this research shows that there are differences in controlling between act on cooperative and act on the micro-finance institution. The way of controlling, according to act on cooperative emphasizes principles to give autonomy, independency, and leniency to a cooperative. Whereas, the controlling model which implemented by OJK emphasize on prudential banking principles.